Believability: sexual violence, media, and the politics of doubt - Banet-Weiser, Sarah (polity, 2023)
"The #MeToo movement created more opportunities for women to speak up about sexual assault. But we are also living in a time when "fake news" and "alternative facts" call into question the very nature of truth. This troubling paradox is at the heart of this compelling book. The convergence of #MeToo and the crisis of post-truth is used to explore the experience of women and people of color whose claims around issues of sexual violence are often held in doubt. Banet-Weiser and Higgins investigate how the gendered and racialized logics of "believability" are defined and contested within media culture, proposing that a mediated "economy of believability" is the context in which public bids for truth about sexual violence are made, negotiated, and authorized today. Believability is a provocative intervention that will appeal to scholars and students across the social sciences and humanities, as well as to general readers."--Provided by publisher